Digital transformation in market research in Peru: a quantitative analysis of process optimization, technological innovation, and customer empowerment - Callupe-Cueva, Paulo César; Aliaga-Miranda, Augusto; Flores-Vilcapoma, Luis Ricardo; Raqui-Ramirez, Christian Efrain; Vila-Hinojo, Bernabé Teodoro; Chavarry-Becerra, Wilmar Salvador (Brazilian Journal of Operations & Production Management, 2025)
Goal: This study explores the impact of digital transformation on market research companies in Huancayo, Peru, focusing on three critical dimensions: process optimization, technological innovation, and customer empowerment. The objective is to understand how these elements collectively enhance competitiveness and organizational adaptability in dynamic and resource-constrained environments. Design / Methodology / Approach: A quantitative, cross-sectional design was employed, utilizing multiple regression and correlation analyses. Data were collected from 30 companies, representing the majority of market research firms in Huancayo, where the total population does not exceed 50. The methodological framework incorporated structured surveys and Ordinary Least Squares (OLS) estimations, with robust validation procedures and adherence to statistical assumptions. A power analysis based on Cohen’s criteria confirmed a high level of statistical power despite the modest sample size. Results: The findings reveal that 88.7% of the variability in process optimization is explained by independent variables, with technological innovation showing the strongest impact (coefficient: 0.743, p<0.001). Customer empowerment, with the highest mean (17.87) and a strong correlation to digital technologies (0.859), underscores the shift towards customer-centric strategies. Limitations of the Investigation: The cross-sectional nature of the study restricts causal inference, and the limited sample size—though representative of the local population—may reduce generalizability and sensitivity to subtle effects. Future studies should employ longitudinal designs and larger samples across multiple regions to validate and extend these results. Practical Implications: The study underscores the importance of integrating digital tools to enhance operational efficiency, foster continuous innovation, and strengthen client engagement. For firms in emerging markets like Peru, particularly in mid-sized cities such as Huancayo, cultivating a culture of digital adaptability and investing in human capital are essential steps toward sustainable competitiveness in the digital era. Originality / Value: By analyzing digital transformation through a multi-dimensional lens, this research contributes to the literature by providing actionable insights into leveraging technology for operational efficiency and customer empowerment in a developing economy context.